Prevalence of tooth loss, bleeding on probing and malocclusion as oral disease indicators in Costa Rican male adolescents : a cross sectional study = Prevalencia de la pérdida de piezas dentales, del sangrado al sondeo y la maloclusión como indicadores de enfermedades orales en adolescentes varones costarricenses : un estudio transversal - Barahona Cubillo, Juan Bautista 1980-
The evidence to characterize oral health during adolescence in Costa Rica is limited. This lack of adequate research makes it difficult to develop appropriate health policies for this subgroup of the population. This is particularly important because adolescence is the period during which good health habits must take root in order to foster good physical and cognitive development. This study aims to determine the prevalence of tooth loss, bleeding on probing and malocclusion in Costa Rican male adolescents at the "Colegio Técnico Profesional San Agustín" (St. Augustine's Technical High School) located in the province of Cartago. Data was collected from 428 male adolescents aged 12-22 years in a cross-sectional study during 2019. Prevalence of tooth loss was calculated as the number of individuals having lost at least one tooth. The average number of teeth lost by individuals was also recorded. The bleeding on probing was an indicator used as a proxy parameter for monitoring periodontal health where the presence of bleeding on probing and calculus was also recorded. Malocclusion was measured using the Dental Aesthetic Index (DAI). The results showed that the prevalence of tooth loss, bleeding on probing and malocclusion was of 19%, 70.0% and 98%, respectively. It was also found that 81% of the participants had all their teeth, 11% had lost 1 tooth, 8% had lost more than one tooth of which 0.5% had lost more than 5 teeth. Considering a general classification of periodontal problems based on bleeding on probing and presence of calculus, the prevalence of periodontal problems increases to 92%. Regarding the DAI, the category identifying a very severe malocclusion was the most prevalent in the sample (88%). It is alarming the high prevalence of tooth loss, bleeding on probing, and malocclusions in a sample of Costa Rican male adolescents, compared to similar studies in other countries. The overarching conclusion of this study is that oral diseases...